2003
DOI: 10.1002/hec.805
|View full text |Cite
|
Sign up to set email alerts
|

What difference does the choice of SES make in health inequality measurement?

Abstract: SummaryThis Note explores the implications for measuring socioeconomic inequality in health of choosing one measure of SES rather than another. Three points emerge. First, whilst similar rankings in the two the SES measures will result in similar inequalities, this is a sufficient condition not a necessary one. What matters is whether rank differences are correlated with health-if they are not, the measured degree of inequality will be the same. Second, the statistical importance of choosing one SES measure ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
118
2
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(125 citation statements)
references
References 14 publications
4
118
2
1
Order By: Relevance
“…Education could provide an important socio-economic influence on health-related behaviour as it may increase the use of health-related information (32) . Although some other SES indicators, mainly occupational position and income, have been shown to have an impact on food intake (33)(34)(35)(36)(37) , parental education level, especially maternal education level, has been strongly related to children's dietary habits (14,38,39) and to childhood overweight and obesity (13,40,41) . An important strength of the present study is its large sample size and international multicentric nature, which allowed us to investigate the research question in different cultural settings with a wider variety of food consumption patterns.…”
Section: Discussionmentioning
confidence: 99%
“…Education could provide an important socio-economic influence on health-related behaviour as it may increase the use of health-related information (32) . Although some other SES indicators, mainly occupational position and income, have been shown to have an impact on food intake (33)(34)(35)(36)(37) , parental education level, especially maternal education level, has been strongly related to children's dietary habits (14,38,39) and to childhood overweight and obesity (13,40,41) . An important strength of the present study is its large sample size and international multicentric nature, which allowed us to investigate the research question in different cultural settings with a wider variety of food consumption patterns.…”
Section: Discussionmentioning
confidence: 99%
“…Stunting is a cause of public concern in many developing countries, and reducing stunting prevalence is one of the key components of improving child health. These three indicators have been commonly used in previous literatures for assessing the health status of children (Table A3) [7,9,24,25]. …”
Section: Methodsmentioning
confidence: 99%
“…A systematic review found 1 While we continue using the expression 'SES' as a comprehensive proxy, we emphasise that the precise choice of SES (i.e. income, education, occupation, or others) may make a great difference both in the assessment of the extent of socio-economic inequalities in health (Wagstaff and Watanabe, 2003) as well as for policy implications (Deaton, 2002). 2 Transitory fluctuations in income may only have a small influence on health (Contoyannis et al, 2004), compared with the strong influence of long term income (Case et al, 2001).…”
Section: Assessing Causalitymentioning
confidence: 99%